2000
DOI: 10.1523/jneurosci.20-17-06540.2000
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-G1: a Novel Glycosyl Phosphatidylinositol-Linked Mammalian Netrin That Is Functionally Divergent from Classical Netrins

Abstract: UNC-6/netrins compose a small phylogenetically conserved family of proteins that act as axon guidance cues. With a signal sequence trap method, we isolated a cDNA encoding a novel member of the UNC-6/netrin family, which we named netrin-G1. Unlike classical netrins, netrin-G1 consists of at least six isoforms of which five were predominantly anchored to the plasma membrane via glycosyl phosphatidyl-inositol linkages. Netrin-G1 transcripts were first detected in midbrain and hindbrain regions by embryonic day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 52 publications
3
133
0
2
Order By: Relevance
“…2B). Several of these mRNAs are known to be have roles in brain function, including Ntng1 (Nakashiba et al 2000), Dlgh2/ PSD93 (Tao et al 2003;Parker et al 2004), Nell2 (Matsuyama et al 2004), and Gabrg2 (Gunther et al 1995). Clearly, it will be interesting to follow up in future studies whether the ncRNAs identified here play any role in the biology of the mRNAs whose expression patterns they share.…”
Section: Tissue Profiling Of Putative Ncrnasmentioning
confidence: 85%
“…2B). Several of these mRNAs are known to be have roles in brain function, including Ntng1 (Nakashiba et al 2000), Dlgh2/ PSD93 (Tao et al 2003;Parker et al 2004), Nell2 (Matsuyama et al 2004), and Gabrg2 (Gunther et al 1995). Clearly, it will be interesting to follow up in future studies whether the ncRNAs identified here play any role in the biology of the mRNAs whose expression patterns they share.…”
Section: Tissue Profiling Of Putative Ncrnasmentioning
confidence: 85%
“…Furthermore, Ntng1 proteins lack any appreciable affinity to receptors for classical netrins. 10 Ntng1 transcripts are most abundant in the CNS with highest expression in the dorsal thalamus, olfactory bulb, and inferior colliculus. Interestingly, Ntng1 is also expressed in the cerebellar inferior olive nuclei, and Figure 4 Expression analysis of NTNG1 in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of a mouse ortholog of chick Netrin-2, cDNA clones encoding three additional mouse Netrins have recently been isolated (Puschel, 1999;Nakashiba et al, 2000;Yin et al, 2000). While Netrin-3 (Puschel, 1999; and Netrin-G1, a novel glycosyl phosphatidylinositol (GPI)-linked Netrin (Nakashiba et al, 2000) are not expressed at the ventral midline of the developing spinal cord, mouse Netrin-4 is selectively expressed at the lateral margins of the floor plate (Yin et al, 2000). Thus, Netrin-4 is well-positioned to potentially function as a long-range chemoattractant for a subpopulation of commissural axons in the netrin-1 knockout mice.…”
Section: Long-range Guidance To the Midline Vertebrate Spinal Cord: Nmentioning
confidence: 99%